Characterization of Electronic and Ionic Transport in Li1-xNi0.8Co0.15Al0.05O2 (NCA). Issue 7 (28th March 2015) - Amin, Ruhul; Ravnsbæk, Dorthe Bomholdt; Chiang, Yet-Ming
Abstract : Despite the extensive commercial use of Li1- x Ni0 . 8 Co0.15 Al0.05 O2 (NCA) as the positive electrode in Li-ion batteries, and its long research history, its fundamental transport properties are poorly understood. These properties are crucial for designing high energy density and high power Li-ion batteries. Here, the transport properties of NCA are investigated using impedance spectroscopy and dc polarization and depolarization techniques. The electronic conductivity is found to increase with decreasing Li-content from ∼10 −4 Scm −1 to ∼10 −2 Scm −1 over x = 0.0 to 0.6, while lithium ion conductivity is at least five orders of magnitude lower for x = 0.0 to 0.75. A surprising result is that the lithium ionic diffusivity vs. x shows a v-shaped curve with a minimum at x = 0.5, while the unit cell parameters show the opposite trend. This suggests that cation ordering has greater influence on the composition dependence than the Li layer separation, unlike other layered oxides. From temperature-dependent measurements in electron-blocking cells, the activation energy for lithium ion conductivity (diffusivity) is found to be 1.25 eV (1.20 eV). Chemical diffusion during electrochemical use is limited by lithium transport, but is fast enough over the entire state-of-charge range to allow charge/discharge of micron-scale particles at practical C-rates.